2022
DOI: 10.7759/cureus.31520
|View full text |Cite
|
Sign up to set email alerts
|

Superficial Circumflex Iliac Artery Free Flap for Coverage of Hand Injuries

Abstract: Open de-gloving hand injuries with exposed tendons and bones require coverage by a flap. Conventionally used groin or abdominal flaps are cumbersome to patients due to extensive dressing and prolonged passive positioning of the hand until pedicle division. Superficial circumflex iliac artery (SCIA) flap is evolved from a traditional groin flap, and because of its thinness, pliability, and concealed donor site, it is an ideal option for single-stage reconstruction of traumatic hand defects avoiding discomfortin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
2
0
0
Order By: Relevance
“…In agreement with our study (Hussain et al, (2022). Found that the use of the pedicled groin flap in hand reconstruction more frequently in elderly patients [11].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In agreement with our study (Hussain et al, (2022). Found that the use of the pedicled groin flap in hand reconstruction more frequently in elderly patients [11].…”
Section: Discussionsupporting
confidence: 92%
“…In line with our findings, Kayano et al (2012) reported that the reconstructive time, defined as the time taken for the surgery in minutes, was longer for the Free ALT flap group, with a mean of 392 minutes compared to 105 minutes for the Pedicled groin flap group [11].…”
Section: Discussionsupporting
confidence: 87%